2004
DOI: 10.2337/diacare.27.12.2797
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Type 2 Diabetes at an Older Age

Abstract: OBJECTIVE -To compare the mortality of people who were diagnosed with type 2 diabetes over 65 years of age with that of nondiabetic individuals. RESEARCH DESIGN AND METHODS-Using a population-based diabetes information system for an observational cohort study in Tayside, Scotland, people who were diagnosed with type 2 diabetes over the age of 65 years between 1993 and 2002 were identified. Nondiabetic comparators, matched for age and sex, were identified from the nondiabetic population. The two cohorts were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 15 publications
4
23
1
2
Order By: Relevance
“…However, although the prevalence of diabetes is greater in the older ages groups, the excess mortality may fall. Tan and colleagues 102 found that in men diagnosed with T2DM over the age of 65 years in Tayside, there was no excess mortality compared with the general population. This might represent a survival selection effect.…”
Section: Stage 1 -Selection By Risk Factorsmentioning
confidence: 99%
“…However, although the prevalence of diabetes is greater in the older ages groups, the excess mortality may fall. Tan and colleagues 102 found that in men diagnosed with T2DM over the age of 65 years in Tayside, there was no excess mortality compared with the general population. This might represent a survival selection effect.…”
Section: Stage 1 -Selection By Risk Factorsmentioning
confidence: 99%
“…A recent report indicated that MS did not predict NOD in a middle-aged Chinese population 18) ; however, the effectiveness of MS to predict NOD in older adults remains uncertain. The clinical significance of DM onset at later age has been challenged 19) ; therefore, using a diagnosis of MS to predict NOD in the elderly population may be logically problematic. In spite of the aforementioned challenges, MS is reported to be closely associated with coronary artery disease and cerebrovascular events in elderly Turks, which supported the benefits of diagnosing MS in older adults 20) .…”
Section: Introductionmentioning
confidence: 99%
“…39 Thus the memductance state can be controlled either by optical or electrical pulses or by combinations of both, which allows the integration with photodetectors as sensory neurons. The conductance control is further sensitive to the wavelength of incoming light 51 , which was also demonstrated with other memristors 52 and memcapacitors 53 and enables encoding information in the wavelength. For the present device, the light sensitivity leads to varying learning processes in the dark and under illumination, which is the key advantage compared to other memristor realization with large on/off ratios of up to 10 12 , 54 low switching times in the sub-nanosecond range 55 or high endurance (10 12 cycles).…”
Section: Discussionmentioning
confidence: 95%